Genetic Architecture and Candidate Genes for Pubescence Length and Density and Its Relationship With Resistance to Common Cutworm in Soybean - Li, Yawei; Chu, Li; Liu, Xiaofeng; Zhang, Nannan; Xu, Yufei; Karikari, Benjamin; Wang, Yu; Chang, Fangguo; Liu, Zexinan; Tan, Lianmei; Yue, Han; Xing, Guangnan; et al. (Frontiers in Plant Science, 2022)
Soybean pubescence play an important role in insect resistance, drought tolerance as well as other stresses. Hence a deep understanding of the molecular mechanism underlying pubescence is a prerequisite to a deeper understanding of insect resistance and drought tolerance. In present study, quantitative trait loci (QTLs) mapping of pubescence traits was performed using a high-density inter-specific linkage map of one recombinant inbred line (RIL) population, designated NJRINP. It was observed that pubescence length negatively correlated with density. A total of ten and nine QTLs distributed on six and five chromosomes were identified with phenotypic variance (PV) of 3.0 % to 9.9 % and 0.8 % to 15.8 % for pubescence length and density, respectively, out of which, eight and five were novel. Most decreased pubescence length (eight of ten) and increased pubescence density (eight of nine) alleles were from the wild soybean PI 342618B. Based on gene annotation, Protein ANalysis THrough Evolutionary Relationships and literature search, 21 and 12 candidate genes were identified related to pubescence length and density, respectively. In addition, Glyma.12G187200 from main QTLs qPL-12-1 and qPD-12-2 was identified as Ps (sparse pubescence) before, having an expression level of five folds greater in NN 86-4 than in PI 342618B, hence it might be the candidate gene that is conferring both pubescence length and density. Based on gene expression and cluster analysis, three and four genes were considered as the important candidate genes of pubescence length and density, respectively. Besides, leaves with dense and short pubescence which are similar to the wild soybean pubescence morphology had the highest resistance to common cutworm in soybean. In conclusion, the findings in present study provide better understanding of genetic basis and candidate genes information of pubescence length and density, as well as the relationship with resistance to common cutworm in soybean.